Implementasi IUD Virtual Learning Media (I-VLAM) terhadap Pengetahuan dan Sikap pada IUD Pasca Persalinan - Toifah, Umi; Widyawati, Melyana Nurul; Suryono, Suryono (Journal of Telenursing (JOTING), 2024)
This research aims to increase the knowledge and attitudes of third-trimester pregnant women towards postpartum IUDs through the application of I-VLAM. The research method used was an actual experiment with a pretest-posttest control group design. The research results show that applying I-VLAM to pregnant women in the third trimester significantly influences increasing knowledge (value = 0.0001) and attitudes (value = 0.0001) toward postpartum IUDs. In conclusion, the application of I-VLAM to pregnant women in the third trimester has been proven to increase knowledge and attitudes towards postpartum IUDs.This research aims to increase the knowledge and attitudes of third-trimester pregnant women towards postpartum IUDs through the application of I-VLAM. The research method used was an actual experiment with a pretest-posttest control group design. The research results show that applying I-VLAM to pregnant women in the third trimester significantly influences increasing knowledge (value = 0.0001) and attitudes (value = 0.0001) toward postpartum IUDs. In conclusion, the application of I-VLAM to pregnant women in the third trimester has been proven to increase knowledge and attitudes towards postpartum IUDs. Keywords: E-Learning, IUD, Postpartum Contraception, Health Promotion